(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
The objective of this paper is to provide data users with a worldwide assessment of the age reporting in the Tanzania Population Census 2012 data. Many demographic and socio-economic data are age-sex attributed. However, a variety of irregularities and misstatements are noted with respect to age-related data and less to sex data because of its biological differences between the genders.